Oil lamp incubators - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
A simple, three-level box can serve as an incubator for farmers who are raising chickens. The eggs are placed on a tray in the middle, wet sand to maintain humidity levels is kept on the bottom, and a container of water is placed on the top as...